Student-Teachers’ intention to adapt existential pedagogy to teach religious and moral education: A survey of affiliated colleges of education to the University of Cape Coast - Eshun Theophilus (University of Cape Coast, 2024)
The study examined Religious and Moral Education (RME) student-teachers’ intention to adapt the Existential Pedagogy to teach RME. The cross-sectional survey design was employed for the study. The proportionate sampling technique involved 183 respondents who answered a questionnaire. Descriptive (frequencies, percentages, means and standard deviations) and inferential (simple linear regression) statistics were used to analyse the data. Findings indicated that RME student-teachers have high intention to adapt existential pedagogy to teach RME. They also had high knowledge level of the pedagogy; however, attitude, subjective norm and perceived behaviour control towards adapting the pedagogy were all moderate. Their knowledge level of the pedagogy had statistically significant positive influence on attitude, subjective norm and perceived behaviour control towards adapting existential pedagogy. Again, attitude, subjective norm and perceived behaviour control towards adapting existential pedagogy had statistically significant positive influences on their intention to adapt the pedagogy. As part of their education and practices, stakeholders, including institutions such as the Colleges of Education, Ghana Education Service, National Council for Curriculum and Assessment, University of Cape Coast, National Schools Inspectorate Authority, and National Teaching Council should consider encouraging student-teachers to use the pedagogy; create awareness of the pedagogy’s use, assist improvisation of available instructional and technological resources, review the indoctrinatory and teacher-centered milieu and the Methods of Teaching RME curriculum, as well as regularise teaching practices, supervisions and monitoring activities set to assist the implementation of RME curriculum for basic schools in Ghana.
xii,249p:,ill
Keywords: Religious and Moral Education (RME) Student-teachers Theory of Planned Behaviour Intention Attitude Subjective Norm Perceived Behaviour Control Knowledge level Existential Pedagogy